DESIGN AND DEVELOPMENT OF AUDIO BASED INTERACTIVE GAME USING ADDIE MODEL - Tony Wibowo; Patrick Chuang (Universitas Internasional Batam, 2022)
Audio Games (AG) are electronic games that employ sound as the main carrier of information. Recently there has been an increasing interest in targeting wider audience, a trend largely due to the development of cellular technology. The target of the audience are visually impaired people because they are also one of the main markets in AG because video games have a dependence on visual information, where video games require sensory abilities that are not possessed by the visually impaired people. This research was conducted to help design and develop interactive audio based video games for wide audience. The method used for the development of this video is the ADDIE method. The result of this research consist of the prototype audio game development using the proposed applied methodology. In this research, there will be also satisfactory accessibility interview of a few visually impaired people.